Armenian-Russian relations in the spring and summer of 1920 in the context of the Armenian side's failures - Hayruni, Ashot (History and Culture, 2025)
Prime Minister of the Republic of Armenia, H. Ohanjanyan, and his government, by unilaterally tying the resolution of the Armenian Question to the Paris Peace Conference and the Treaty of Sèvres, failed to assess the real opportunities that Russia's return to the region presented for Armenia. In June 1920, Russia prohibited Kemal from attacking Armenia while simultaneously pressuring him to accept its mediation in delineating the border between Armenia and Turkey. However, the Armenian government not only refused to accept Russia's mediation but also consistently failed to establish bilateral relations with Russia. This was despite Russia's promises to allocate certain territories from Western Armenia to the Republic of Armenia. By shortsightedly rejecting Russia's military-political support, the Armenian side effectively gave the Kemalists the green light to launch an attack on Armenia.The widely held view among us that Armenia became a victim of the Kemalist-Bolshevik alliance does not correspond to reality. Had the opportunities presented by Russia been realistically assessed and utilized, not only could the Kemalist invasion of Armenia have been prevented, but Armenia's territory might also have been significantly expanded.